Analysis of the Implementation of Blended Learning with Google Classroom as a Language Learning Media - Nur Alifah (National Conference on Language, Education, and Technology Proceeding, 2023)
The Covid-19 pandemic has impacted education and made teaching and learning activities use blended learning and Google Classroom as learning media. This research aims to determine the implementation of blended learning using Google Classroom as a language learning media. The method used in this research is descriptive qualitative. The research results indicate that using Google Classroom as a platform for implementing Blended Learning at SMP X is common and aims to make learning easier for students. In conclusion, Blended Learning with Google Classroom can improve language learning. However, it is necessary to consider the challenges and recommendations mentioned to achieve optimal results in technology-based education